2022
DOI: 10.1155/2022/9001881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levothyroxine Sodium Tablets on Pregnancy Outcome and Offspring Development Quotient of SCH during Pregnancy

Abstract: Objective. To investigate the effect of levothyroxine sodium tablets (L-T4) on pregnancy outcome and offspring development quotient in patients with subclinical hypothyroidism (SCH) during pregnancy. Material and Methods. Pregnant women with gestational age less than 12 weeks who underwent the first prenatal examination in our hospital from January 2019 to December 2019 were prospectively selected as subjects. According to the level of thyroid hormone in pregnant women, they were divided into the treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…A previous study suggested that levothyroxine improves pregnancy-related outcomes in patients with subclinical hypothyroidism as well as the neurointellectual development of newborns [29]. In contrast, we found no significant difference in NICU requirement, mode of delivery, gestational week at birth, mean age, and infant gender according to the maternal use of levothyroxine.…”
Section: Discussioncontrasting
confidence: 87%
“…A previous study suggested that levothyroxine improves pregnancy-related outcomes in patients with subclinical hypothyroidism as well as the neurointellectual development of newborns [29]. In contrast, we found no significant difference in NICU requirement, mode of delivery, gestational week at birth, mean age, and infant gender according to the maternal use of levothyroxine.…”
Section: Discussioncontrasting
confidence: 87%
“…However, the results of other studies are different from those of this study. One study about the effect of LT4 on pregnancy outcomes and offspring development quotient in patients with SCH during pregnancy showed that LT4 not only improved the pregnancy outcome of SCH during pregnancy but also improved the neuro-intellectual development of offspring [13]. A meta-analysis on the association between maternal SCH and growth, development, and childhood intelligence showed that maternal SCH was associated with delayed intellectual and motor development of offspring [5].…”
Section: Discussionmentioning
confidence: 99%